Aplikasi Seluler untuk Pencegahan Insiden Keselamatan Pasien Anak - Endang Puspita Sari; Sigit Mulyono (Journal of Telenursing (JOTING), 2023)
This study aims to determine the role of mobile applications in preventing safety incidents for pediatric patients in hospitals. The method used was a literature search through searching the online databases Science Direct, ProQuest, Scopus, and Google Scholar published in 2018-2022 with the keywords mobile application, patient safety, child, hospitalized, and patient education. The research results showed that children's safety awareness levels increased after being given a safety incident prevention program using a mobile application. In conclusion, mobile applications for preventing pediatric patient safety incidents in hospitals are practical, feasible, and acceptable to children, families, and nurses. Keywords: Children, Mobile Applications, Patient Safety, Safety Incident Prevention, Pediatric Nurses